The Importance of Urban Greenery in the Construction of a Smart Landscape to Reduce Negative Environmental and Climate Impacts - Amanda Fruehauf; Paulo Pellegrino; Magda Lombardo (Environmental Science and Sustainable Development)
The intense urbanization of the Municipality of São Paulo, SP, Brazil, highlights the high soil sealing, the reduction of open spaces, hinders stormwater runoff, and intensifies the process of Urban Heat Island. The objective of the work is to evaluate the importance of Urban Greenery analysis in order to contribute to a balanced system of permeable surfaces and urban afforestation, collaborating to a sustainable drainage system and cooling of the Urban Heat Island. Thus, the use of geo-technologies was used to obtain the maps of land use and occupation, Vegetation Index, and Land Surface Temperature and also statistics on the data and thus analyze the landscape in search of Nature-based Solutions. The analysis and implementation of Green Infrastructure in this research focuses on medium and large-sized street afforestation, and this must present harmony with all the city's infrastructure, collaborating with the environmental systems. The work can contribute to rethinking the green areas, with emphasis on Planting trees in cities to improve air quality, and reduce heat island effects, in order to build a smart landscape that aims to mitigate negative environmental and climate impacts, for the entire Municipality of São Paulo and thus meet the Nature-based Solutions.